Quantifying the Likelihood of False Positives: Using Sensitivity Analysis to Bound Statistical Inference - Thomas, Kyle J. (Journal of quantitative criminology, 2019)
Criminologists have long questioned how fragile our statistical inferences are to unobserved bias when testing criminological theories. This study demonstrates that sensitivity analyses offer a statistical approach to help assess such concerns with two empirical examples—delinquent peer influence and school commitment.